Market-oriented Yam Storage - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
GTZ Root and Tuber Development Guides (2); Reducing Losses and Increasing Income. GTZ. 1999.8 pp.Free of chargeAlbert Bell, section 4541, GTZ,PO Box 5180, D-65726 Eschborn, GermanyFax: + 49 6196 79 65 54Email: albert.bell@gtz.de